2018
DOI: 10.1097/tp.0000000000002117
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of HLA Molecular Mismatch Methods to Determine HLA Immunogenicity

Abstract: BackgroundAntibody-mediated rejection is a major cause of premature graft loss in kidney transplantation. Multiple scoring systems are available to assess the HLA mismatch between donors and recipients at the molecular level; however, their correlation with the development of de novo donor-specific antibody (dnDSA) has not been compared in recipients on active immunosuppression.MethodsHLA-DRβ1/3/4/5/DQα1β1 molecular mismatch was determined using eplet analysis, amino acid mismatch, and electrostatic mismatch f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 19 publications
4
70
0
Order By: Relevance
“…The authors furthermore did not demonstrate any advantage in using the eplet approach over enumerating the number of different amino acids (AAMS) to assess the risk of DSA development. Wiebe et al confirmed these results in a large cohort (N = 596) evaluating the prediction capacity for the development of HLA‐DR/DQ dn DSA . Among the 6 approaches tested in the current study, the highest C ‐index was observed with the AAMS, albeit only marginally higher than that observed with the other techniques.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The authors furthermore did not demonstrate any advantage in using the eplet approach over enumerating the number of different amino acids (AAMS) to assess the risk of DSA development. Wiebe et al confirmed these results in a large cohort (N = 596) evaluating the prediction capacity for the development of HLA‐DR/DQ dn DSA . Among the 6 approaches tested in the current study, the highest C ‐index was observed with the AAMS, albeit only marginally higher than that observed with the other techniques.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have demonstrated significant correlations between eplet load (via HLA Matchmaker) of HLA mismatches and the development of DSA class I and class II as well as allograft outcomes . However, to the best of our knowledge, only two recent studies, conducted by Kosmoliaptsis et al and Wiebe et al, compared the two approaches provided by Duquesnoy et al and Kosmoliaptsis et al…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether unique effector functions of IgG4 subclass DSA in the presence of higher HLA expression directly contributed to the subclinical histopathology phenotypes observed in these studies or whether a predominant IgG4 subclass serves solely as a biomarker of a prolonged smoldering humoral response. It is important to recall that higher HLA eplet mismatch loads were observed with DSA presence and strength, as previously reported,[31][32][33] and also with IgG4 subclass DSA. This is consistent with a scenario in which higher alloimmune burden drives DSA development and evolution over time to a more mature IgG4 humoral response.Our findings are consistent with other studies that have shown IgG4 DSA in recipients with chronically rejected kidney and liver allografts.…”
supporting
confidence: 75%
“…Patients with detectable class II DSA, compared to those without, had a higher median (interquartile range) total class II eplet mismatch (33 vs 26 ) and HLA-DQ alone mismatch (12 [8][9][10][11][12][13][14][15][16] vs 8 [4][5][6][7][8][9][10][11][12][13][14][15]). Similarly, total class II eplet mismatch was higher for those with MFI sum >20 000 vs ≤20 000 (40 [28-51] vs 28 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]). Among subjects with class II DSA, total class II eplet mismatch was higher for those with maximum MFI > 20 000 vs ≤20 000 (39 vs 30 [21][22][23][24][25][26][27][28][29][30]…”
Section: Incidence and Strength Of Hla Class II Dsamentioning
confidence: 99%
See 1 more Smart Citation